Short-term effects of sports taping on navicular height, navicular drop and peak plantar pressure in healthy elite athletes: A within-subject comparison - Kim, T.; Park, J.-C. (Medicine, 2017)
Medial tibial stress syndrome (MTSS) is one of the most common exercise-induced leg pain. The navicular drop (ND) was identified as a risk factor for MTSS. This study aimed to evaluate the short-term effects of sports taping applied to the supporting lower leg during sitting, standing, walking, and jogging to restrict the ND in healthy elite athletes.